Assessing the impact of care farms on quality of life and offending: a pilot study among probation service users in England. Issue 3 (17th March 2018) - Elsey, Helen; Farragher, Tracey; Tubeuf, Sandy; Bragg, Rachel; Elings, Marjolein; Brennan, Cathy; Gold, Rochelle; Shickle, Darren; Wickramasekera, Nyantara; Richardson, Zoe; Cade, Janet; Murray, Jenni
Abstract : Objectives: To assess the feasibility of conducting a cost-effectiveness study of using care farms (CFs) to improve quality of life and reduce reoffending among offenders undertaking community orders (COs). To pilot questionnaires to assess quality of life, connection to nature, lifestyle behaviours, health and social-care use. To assess recruitment and retention at 6 months and feasibility of data linkage to Police National Computer (PNC) reconvictions data and data held by probation services. Design: Pilot study using questionnaires to assess quality of life, individually linked to police and probation data. Setting: The pilot study was conducted in three probation service regions in England. Each site included a CF and at least one comparator CO project. CFs are working farms used with a range of clients, including offenders, for therapeutic purposes. The three CFs included one aquaponics and horticulture social enterprise, a religious charity focusing on horticulture and a family-run cattle farm. Comparator projects included sorting secondhand clothes and activities to address alcohol misuse and anger management. Participants: We recruited 134 adults (over 18) serving COs in England, 29% female. Results: 52% of participants completed follow-up questionnaires. Privatisation of UK probation trusts in 2014 negatively impacted on recruitment and retention. Linkage to PNC data was a more successful means of follow-up, with 90% consenting to access their probation and PNC data. Collection of health and social-care costs and quality-adjusted life year derivation were feasible. Propensity score adjustment provided a viable comparison method despite differences between comparators. We found worse health and higher reoffending risk among CF participants due to allocation of challenging offenders to CFs, making risk of reoffending a confounder. Conclusions: Recruitment would be feasible in a more stable probation environment. Follow-up was challenging; however, assessing reconvictions from PNC data is feasible and a potential primary outcome for future studies.